2019
DOI: 10.5812/semj.87532
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling of Depression and Its Related Factors Using a Spatial Generalized Linear Mixed Model in Mashhad, Iran: A Cross-Sectional Study

Abstract: Background: Depression is one of the most common mental disorders and it has the third rank of the cause of disability and has been considered to increase the years of life with disability in Iran. Objectives: The purpose of this study was to map the geographical distribution and find hot spots of depression and its relation to demographic and socioeconomic factors in Mashhad. Methods: A population-based cross-sectional study was conducted in Mashhad in 2010. In this study, 9704 individuals aged 35 to 65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…(1990), showed that marital status has no relation to depression. Previous studies, however, have found that single individuals are more likely to become depressed than married ones, regardless of whether they have lost loved ones (Bulloch et al., 2017; Hadianfar et al., 2019). The pattern of depression in relatives of person died by brain death appears to be different from that of depression in another comprehensive study, and further studies are needed to clarify the unknown dimensions of depression among them.…”
Section: Discussionmentioning
confidence: 90%
“…(1990), showed that marital status has no relation to depression. Previous studies, however, have found that single individuals are more likely to become depressed than married ones, regardless of whether they have lost loved ones (Bulloch et al., 2017; Hadianfar et al., 2019). The pattern of depression in relatives of person died by brain death appears to be different from that of depression in another comprehensive study, and further studies are needed to clarify the unknown dimensions of depression among them.…”
Section: Discussionmentioning
confidence: 90%
“…Further, it was estimated that by 2020, MDD would have been the second most common disease after cardiovascular diseases [ 3 ]. In this line, a national study in Iran showed that the prevalence rates of MDD were almost 20%, and MDD was considered one of the most impacting health problems in Iran [ 4 ].…”
Section: Introductionmentioning
confidence: 99%